The Advantages of Factor Analysis as a Method of Testing Questionnaires in Health Research - Heru Santoso Wahito Nugroho; Abdullah Al Mamun; Tanko Titus Titus Auta; Bahtiar Bahtiar; Sanglar Polnok; Joel Rey Ugsang Acob; Hammad Hammad; I Putu Suiraoka; Ragu Harming Kristina (Alliance oh Health Activists (AloHA), 2025)
Questionnaires are a data collection method that is widely used in health research. Nowadays, the validity test that is often used to assess the quality of questionnaires is the item-total correlation test. This study aims to introduce another method that is often said to be better by experts, namely factor analysis. When compared with item-total correlation analysis, factor analysis has the advantages of: 1) it can reveal the latent structure of the variables being measured; 2) can capture multivariate variations; 3) can test construct validity, namely whether the questionnaire is able to measure concepts or constructs theoretically; 4) can determine how many factors are needed to explain the variance in the data. It was concluded that taking into account its advantages, factor analysis is the best choice for testing the validity of questionnaires in health research. Keywords: health research; questionnaire; validity test; categorical variables; factor analysis